Impact of Microplastics on Ciprofloxacin Adsorption Dynamics and Mechanisms in Soil - Qian Xu; Hanbing Li; Sumei Li; Ziyi Li; Sha Chen; Yixuan Liang; Yuyang Li; Jianan Li; Mengxin Yuan (Toxics)
The co-occurrence of microplastics (MPs) and antibiotics as emerging contaminants demonstrates significant ecological perturbations in soil matrices. Of particular scientific interest is the potential for MPs to mediate the environmental fate and transport dynamics of co-existing antibiotics. This study investigated MP-mediated ciprofloxacin (CIP) adsorption in lateritic soils. Batch experiments with polyethylene (PE), polypropylene (PP), and poly (ethylene-terephthalate) (PET) revealed soil components dominated CIP retention, while 10% (w/w) MPs reduced soil adsorption capacity by ≥10.8%, with inhibition intensity following PET > PE > PP. Adsorption thermodynamics exhibited significant pH dependence, achieving maximum sorption efficiency at pH 5.0 (± 0.2), which was approximately 83%. Competitive adsorption analysis demonstrated inverse proportionality between ionic strength and CIP retention, with trivalent cations exhibiting superior competitive displacement capacity compared to mono- and divalent counterparts. Isothermal modeling revealed multilayer adsorption mechanisms governed by hybrid chemisorption/physisorption processes in both soil and MP substrates. Spectroscopic characterization suggested differential adsorption pathways: MP-CIP interactions were primarily mediated through hydrophobic partitioning and π-π electron coupling, while soil–MP composite systems exhibited dominant cation exchange capacity and surface complexation mechanisms. Notably, electrostatic attraction/repulsion forces modulated adsorption efficiency across all experimental conditions, particularly under varying pH regimes. This work advances understanding of co-contaminant dynamics in soil ecosystems, informing risk assessment frameworks.